The risk sexual behavior of adolescents reviewed based on Health belief model - Puspita Ningrum (Alma Ata University Press, 2021)
ABSTRACTBackground: Sexual behavior is a form of behavior that is carried out to attract attention with the opposite sex and involves a touch on the limbs carried out between men or women so that they reach the stage of intimate relationships. Health belief model (HBM) is one of the patterns in determining the relationship between health beliefs and behavior. The behavior of adolescents who have sexual relations is reviewed using the Health Belief Model theory because it can predict and influence the possibility that adolescents can prevent or not believe in the individual's own beliefs.Objectives: To analyze how the relationship between perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, self-efficacy and cues to action with adolescent sexual behavior based on the Health Belief ModelMethods: This study is a non-experimental study using a cross-sectional approach. The sample in this study were 300 respondents who were conducted at SMA X Kotamobagu by taking purposive sampling technique. The instrument used is a questionnaire. Statistical test using Pearson Product Moment with a=<0.05Results: The majority of respondents showed less behavior as much as 148 (49.3%), the majority of respondents were 17 years old (30.0%), the majority of female respondents were 204 (68.0%). The results of the analysis showed that there was a relationship between perceived susceptibility, perceived barriers, self-efficacy, cues to action p=<0.05 with risky sexual behavior, there was no relationship between perceived seriousness and perceived benefits adolescent with risky sexual behavior.Conclusions: Based on the results of the analysis there is a relationship between perceived susceptibility, perceived barriers, self-efficacy, cues to action with risky sexual behavior p=<0.05, there is no relationship between perceived seriousness and perceived benefits with adolescent risky sexual behavior, the most related variable is cues to action at SMA X Kotamobagu